Method of assessment of information availability of radio inflammation sources by devices of radioelectronic recognition - Yakhno, I.; Malyk, O.; Hatsenko, S.; Shyshatskyi, A.; Pikul, O. (Національний технічний університет "Харківський політехнічний інститут", 2019)
Providing information superiority over the enemy is becoming a prerequisite for conducting military operations. The main type of information support is military intelligence, and its basis is radio-electronic intelligence. During the analysis of the known scientific achievements in the direction chosen by the authors of the researchit was established that at present there is no general methodology for assessing the capabilities of the forces and devices of radio-electronic intelligence for the information (reconnaissance) availability of electronic intelligence sources that is suitable for the use in automation devices of various control units, which connects separate indicators of information accessibility in generalized on the basis of the use of modern intelligence-information models. The authors of this research conducted a methodology for assessing the availability of radio-emission sources by the devices of radio-electronic intelligence. In the course of the research, the authors used the basic provisions of the theory of radio-electronic intelligence, the theory of communication, the theory of electronic warfare, the theory of signals, and general scientific methods ofanalysis and synthesis. The technique developed by the authors makes it possible to evaluate sources of electronic intelligence from the point of view of the expediency of including in the outline the distribution of forces and devices for different conditions of the situation (stages of combat or operations), effectively manage the forces and devices of extraction and processing in the interests of solving radio-electronic intelligence tasks, and evaluate the degree of this efficie ncy. This technique, which is an integral part of the general methodology for the distribution of forces and intelligence, can be applied at the command posts (grouping of troops, military units) of electronic intelligence and will increase the efficiency of conducting searches of sources and objects of electronic intelligence, as well as the distribution of forces and resources for tasks, objects and sources. Inaddition, it can be used to assess the effectiveness of existing and promising devices and complexes of electronic intelligence and electronic warfare. Taking into account the above, the direction of further research should be considered the development of scientific and methodical apparatus for improving the efficiency of conducting radio-electronic intelligence.

Забезпечення інформаційної переваги над противником на сьогодні стає основною умовою для ведення воєнних операцій. Основним видом інформаційного забезпечення є воєнна розвідка, а її основою –радіоелектронна розвідка. В ході проведення аналізу відомих наукових досягнень в обраному авторами дослідження напрямку встановлено, що на даний час відсутня загальна методика оцінки можливостей сил і засобів радіоелектронної розвідки по інформаційній (розвідувальній) доступності джерел радіоелектронної розвідки, що є придатною для використання в засобах автоматизації різних ланок управління, що зв’язує окремі показники інформаційної доступності в узагальнений на основі використання сучасних розвідувально-інформаційних моделей. Авторами зазначеного дослідження було проведено розробку методики оцінки інформаційної доступності джерел радіовипромінювання засобами радіоелектронної розвідки. В ході дослідження авторами були використані основні положення теорії радіоелектронної розвідки, теорії зв’язку, теорії радіоелектронної боротьби, теорії сигналів та загальнонаукові методи аналізу та синтезу. Розроблена авторами методика дозволяє оцінювати джерела радіоелектронної розвідки з точки зору доцільності включення в вихідний план розподілу сил та засобів для різних умов обстановки (етапів бою або операції), ефективно управляти силами і засобами добування і обробки в інтересах вирішення задач радіоелектронної розвідки та оцінювати ступінь цієї ефективності. Дана методика, що є складовою частиною загальної методики розподілу сил і засобів розвідки, може бути застосована на командних пунктах (угруповання військ, військової частини і підрозділу) радіоелектронної розвідки і підвищить ефективність ведення пошуку джерел і об’єктів радіоелектронної розвідки, а також розподілу сил і засобів за завданнями, об’єктамиі джерелами. Крім того, вона може бути використана для оцінки ефективності існуючих та перспективних засобів і комплексів радіоелектронної розвідки і радіоелектронної боротьби. Враховуючи зазначене, напрямком подальших досліджень слід вважати розробку науково-методичного апарату підвищення ефективності ведення радіоелектронної розвідки.
Методика оцінки інформаційної доступності джерел радіовипромінювання засобами радіоелектронної розвідки
Keywords: radio communication systems; radio resources; noise immunity; radio electron suppression; система радіозв’язку; радіоресурс; завадозахищеність; радіелектронне подавлення